Case Report: Serplulimab-induced thyroid dysfunction in a patient with advanced small cell lung cancer - Lu, Lu; Liu, Lingxiang; Fang, Wentong; Liu, Xiaojian (Frontiers in Oncology, 2025)
Studies have shown that the application of immune checkpoint inhibitors (ICIs) in solid tumors can easily affect the endocrine system, causing disorders of thyroid function, which are usually reversible after treatment cessation in most patients. Serplulimab is a PD-1 inhibitor and is used for treating small cell lung cancer (SCLC). Previous adverse reactions mention the impact of Serplulimab on the release and synthesis of thyroid hormones, but the occurrence of hyperthyroidism and hypothyroidism in the same patient has not ever been reported. We hereby report a 78-year-old patient with SCLC who developed severe hyperthyroidism after the second cycle of Serplulimab treatment. This condition lasted for one month and improved to the normal level, but it turned into hypothyroidism without any distinguishing clinical features after using Serplulimab again. The changes of relevant thyroid hormone levels in each cycle should be recorded and corresponding interventions should be implemented based on features and hormone levels. Moreover, it is necessary to combine the baseline characteristics to predict the possible adverse reactions of the patients in advance and conduct pharmacological monitoring as early as possible.